Combination of coronary heart disease, chronic heart failure, and anaemic syndrome: clinical features and prognostic impact of anaemia treatment - T. Yu. Kalyuta; Yu. G. Shvarts; I. M. Sokolov (Российский кардиологический журнал)
Practitioners are often faced with a combination of coronary heart disease (CHD), chronic heart failure (CHF), and anaemic syndrome. These patients are typically characterised by a worse prognosis of acute and chronic CHD, as well as by a rapid progression of CHF and chronic renal failure (CKF).This review is focussed on the epidemiology of anaemia in CHD and CHF patients; the aetiology and pathogenesis of anaemia in CHD and CHF; and the changes of cardiovascular parameters in patients with anaemic syndrome. Despite the abundance of studies on CHD and CHF clinical course and prognosis in anaemic syndrome, very little is known about the effects of anaemia treatment on the clinical course and prognosis of CHD. The review presents the external evidence and original results on the prognosis of acute and chronic CHD in anaemic patients. A modern view on anaemia treatment in various CHD forms is also presented.